2019
DOI: 10.1039/c9re00224c
|View full text |Cite
|
Sign up to set email alerts
|

An efficient process for the Cu(0)-mediated synthesis and subsequent chain extension of poly(methyl acrylate) macroinitiator

Abstract: A process combining a continuous tubular and a semi-batch reactor is established as an efficient method for the synthesis of block copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(41 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Only 23% conversion was reached after 3 h reaction at room temperature with 30 wt% PGME as solvent using an initial MA:MBP:PMDETA molar ratio of 10:1:0.05 (Expt B‐RT‐P‐MBP), whereas conversions were greater than 80% for similar reaction conditions using Me 6 TREN. [ 9 ] In addition, MW analysis indicated that only a small fraction of the MBP in the system successfully initiated chain growth. The addition of ASC increased the conversion to over 90% but resulted in loss of controlled chain growth, while the addition of water as cosolvent promoted reaction rate and improved initiation efficiency, but not to the extent required for the tubular process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 23% conversion was reached after 3 h reaction at room temperature with 30 wt% PGME as solvent using an initial MA:MBP:PMDETA molar ratio of 10:1:0.05 (Expt B‐RT‐P‐MBP), whereas conversions were greater than 80% for similar reaction conditions using Me 6 TREN. [ 9 ] In addition, MW analysis indicated that only a small fraction of the MBP in the system successfully initiated chain growth. The addition of ASC increased the conversion to over 90% but resulted in loss of controlled chain growth, while the addition of water as cosolvent promoted reaction rate and improved initiation efficiency, but not to the extent required for the tubular process.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of ASC increased the conversion to over 90% but resulted in loss of controlled chain growth, while the addition of water as cosolvent promoted reaction rate and improved initiation efficiency, but not to the extent required for the tubular process. While reaction temperature did not provide an improvement in rate or control when Me 6 TREN was used as ligand, [ 9 ] increasing the reaction temperature to 60 °C led to almost complete reaction of the MA (98% conversion) in the batch trials, while simultaneously lowering dispersity ( Ð ) to 2.37 (Table 1, Expt B‐60‐P‐MBP). However, the average chain length of 26 was much higher than the target value of 10, indicating that initiation efficiency with MBP remained low.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations